Dreams in Evagrius Ponticus’ life and teaching - Rivas, Rubén Peretó (Vox Patrum, 2018)
There are few late antiquity authors who pay more attention than Evagrius to dreams. For him, visions and dreams are not a way to prophesy the future or to keep in contact with the dead. They are basically a way to know oneself and the state of one’s own spiritual life. After contextualizing the theories on dreams in the most significant authors of that period, I discuss the place that visions and dreams occupied in the Evagrian corpus, describing their mechanisms as a complex operation between passions, memory and the influence of demons.